Nurturing the public service, security and safety with integrity - Mohamad Yunus, Mohamad Ismail (Institute Of Public Security of Malaysia, 2015)
Integrity is like a mighty tree that stands out in the forest. Its roots are deep, supporting a tall and hardy trunk and its top is a crown of branches and green leaves. It blooms with large clusters of fruit in brilliant colours, ripe and ready to scatter its seeds. Birds and other animals find comfort perching on its secure branches. (Malaysian Institute of Integrity 2010. 1). The main idea of this article is to focus on the public officials in their conduct of public affairs to inculcate such moral values as: integrity, consistency, impartiality, responsibility, accountability, trustworthiness and maintenance of a high degree of ethical and moral standards in ensuring and securing public security and safety in the society. Hence the objective is to generate more who are well informed in the light of the qualities. The community should expect to find in them as public servants with unquestionable integrity, who preserve high ethical standards under all situations and circumstances. As well said by Martin Luther King, the ultimate measure of a man is not where he stands in moments of comfort and convenience, but where he stands at times of challenge and controversy.